Performance Evaluation of Wireless Charger Antenna Design of Mobile Phone - Anton Yudhana; Fahrizal Djohar (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2017)
Using cable as power transmission medium cause problem in flexibility and aesthetics. Wireless power transmission for charging handphone released nowadays still using antenna with radiation pattern focus in one direction, that is just toward the top, and if the antenna was shifted then power transmitted will be lose. The purpose of this research is to produce wireless power charger system used for charging handphone power using resonator based on omnidirectional antenna and test the performance. The device in this research was designed in two main part, that is transmitter and receiver. In transmission section, there is power supply used for supplying power to oscillator to generate oscillating signal in the form of electrical power to be transmitted to receiver via antenna in the form magnetic field. In receiver section, receiver antenna received the power transmitted that is still in the reach of magnetic field generated by transmitter. The power that is still in the form of oscillating signal, then stabilized for the purpose of handphone power using rectifier and voltage regulator.Â Design has been made successfully to the form of handphone battery power wireless charger using omdirectional antenna which consist of two main part, that is transmitter and receiver. The transmitted power is 3.058 watt with frequency 714 KHz, and receiver received the power and then stabilized the signal to produce output power 58.706 miliwatt. This device can transmit power in all directions horizontally (angle 360Â°). This device also tested with some kind of obstacle, with the result almost all obstacle still could transmit the power except metal.